Thinning temporarily stimulates tree regeneration in a restored tropical forest - Oliveira, Carlos Delano Cardoso de [UNESP]; Durigan, Giselda [UNESP]; Putz, Francis Edward (Elsevier, 2021)
When an ecosystem undergoing restoration does not follow the desired trajectory, management interventions may be warranted. Where the initial steps towards restoration include tree planting at high densities, reduction of stand basal area (BA) by overstory thinning is a potential adaptive management tool to stimulate natural regeneration, although it can also damage young plants. We ask how tree regeneration in a restored tropical forest responds to different intensities of thinning. We applied two intensities of thinning to a 22-yr-old restored forest in southeastern Brazil and then sampled seedlings and saplings before and over an eight year period after thinning; unthinned plots were retained as controls. Thinning impacts on the woody understory were negligible, far below annual mortality in control plots. Positive responses to thinning were stronger in the treatment with low remaining basal area (ca. 30% below the reference forests), with increases in seedling density, numbers of recruits, and seedling-to-sapling and sapling-to-tree transitions. Understory dynamics were clearly intensified by gap opening, with a pulse of natural regeneration in the first years after thinning. These changes, however, were not simultaneous and did not usually persist over time. Rarefied richness of the understory increased over time after all treatments and changes in species composition of saplings were enhanced by thinning. Our study gives support to selective timber harvests from restored tropical forests insofar as thinning did not threaten the understory and stimulated natural regeneration. Frequency and intensity of thinning operations, however, should be locally adjusted based on monitoring data.
Keywords: Adaptive management; Forest dynamics; Forest restoration; Forest structure; Restoration thinning; Tree diversity; Tropical silviculture